2022
DOI: 10.1007/s00192-022-05339-7
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of urological injury during caesarean section and hysterectomy

Abstract: Introduction and hypothesis We aim to review iatrogenic bladder and ureteric injuries sustained during caesarean section and hysterectomy. Methods A search of Cochrane, Embase, Medline and grey literature was performed using methods pre-published on PROSPERO. Eligible studies described iatrogenic bladder or ureter injury rates during caesarean section or hysterectomy. The 15 largest studies were included for each procedure sub-type and meta-analyses perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 121 publications
0
1
0
Order By: Relevance
“…And the rate of blood transfusion was higher on patients had severe anaemia particularly on haemoglobin less than 9.5 g/dl which had significant risks as reported by Ehrenthal, et al study (2012) [13]. In recent systematic review (2022) had reported that the overall total numbers of relevant study were 312 bladder injures and 7 ureteric injuries with mean injury rates documented were 267 and 9 events per 100,000 cases respectively [14]. And most of these injuries occurs secondary to caesarean section and hysterectomy [15][16][17].…”
Section: Bowel Injury 0mentioning
confidence: 87%
“…And the rate of blood transfusion was higher on patients had severe anaemia particularly on haemoglobin less than 9.5 g/dl which had significant risks as reported by Ehrenthal, et al study (2012) [13]. In recent systematic review (2022) had reported that the overall total numbers of relevant study were 312 bladder injures and 7 ureteric injuries with mean injury rates documented were 267 and 9 events per 100,000 cases respectively [14]. And most of these injuries occurs secondary to caesarean section and hysterectomy [15][16][17].…”
Section: Bowel Injury 0mentioning
confidence: 87%
“…again, probably due to the overconfidence factor [19]. On the other hand, the use of cystoscopy to detect urinary tract lesions is not completely standardized; There are reports where, despite the existence of blad-der or ureteral lesions, cystoscopy has failed to diagnose them [20]. It is reported that the detection rate is low (1.6 per 1000 surgeries) with the routine use of cystoscopy and 0.7 without the use of cystoscopy; Cystoscopy is not so harmless because its complications include bleeding or injury to the ureter per se, so the risk-benefit of performing it routinely must be assessed; However, there is the other side of the coin, detect it in time [21].…”
Section: Discussionmentioning
confidence: 99%
“…They did not find any other predictors regarding previous surgery, previous radiation, diagnosis, type of surgery or demographics. Wei et al 8 found that surgeon inexperience was the main prime risk for these injuries, and Ali et al 6 found that late diagnosis of IUIs were more common amongst non-specialist surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why younger age and benign indication for hysterectomy predispose for a delayed diagnosis is not clear to us, but one theory that already has been mentioned is surgeon experience 6 , 8 . Our theory is that the more experienced surgeons perform surgery on malignant indication, due to the importance of radical tumour resection.…”
Section: Discussionmentioning
confidence: 99%